LO41: The development of a standardized provincial massive hemorrhage protocol with a built-in continuous quality improvement framework. (May 2020) - Yeh, C.; Cope, S.; Thompson, T.; McGilvray, S.; Petrosoniak, A.; Chin, V.; Karkouti, K.; Nathens, A.; Murto, K.; Beno, S.; McDonald, A.; Beckett, A.; et al.
Abstract : Background: Massive hemorrhage protocols (MHPs) streamline the complex logistics required for prompt care of the bleeding patient, but their uptake has been variable and few regions have a system to measure outcomes from these events. Aim Statement: We aim to implement a standardized MHP with uniform quality improvement (QI) metrics to increase uptake of evidence-based MHPs across 150-hospitals in Ontario between 2017 and 2021. Measures & Design: We performed ongoing PDSA cycles; 1) stakeholder analysis by surveying the Ontario Regional Blood Coordinating Network (ORBCoN), 2) problem characterization and Ishikawa analysis for key QI metrics based on areas of MHP variability in 150 Ontario hospitals using a web-based survey, 3) creation of a consensus MHP via a modified Delphi process, 4) problem characterization at ORBCoN for the design of a freely available toolkit for provincial implementation by expert working groups, 5) design of 8 key QI metrics by a modified Delphi process, and 6) identification of process measures for QI data collection by implementation metrics. Evaluation/Results: PDSA1-2; 150-hospitals were surveyed. 33% of hospitals lacked MHPs, mostly in smaller sites. Major areas for QI were related to activation criteria, hemostatic agents, protocolized hypothermia management, variable MHP naming, QI metrics and serial blood work requirements. PDSA3; 3 Delphi rounds were held to reach 100% expert consensus for 42 statements and 8 CQI metrics. Major areas for modification were protocol name, laboratory resuscitation targets, cooler configurations, and role of factor VIIa. PDSA4; adaptable toolkit is under development by the steering committee and expert working groups. Implementation is scheduled for Spring 2020. PDSA5; the 8 CQI metrics are: TXA administration < 1 h, RBC transfusion < 15 min, call to transfer for definitive care < 60 min, temp >35°C at end of protocol, Hgb kept between 60-110g/L, transition to group-specific RBC by 90 min, appropriate activation defined by ≥6 units RBC in the first 24 hours, and any blood component wastage. Discussion/Impact: MHP uptake, content, and tracking is variable. A standardized MHP that is adaptable to diverse settings decreases complexity, improves use of evidence-based practices, and provides a platform for continuous QI. PDSA6 will occur after implementation; we will complete an implementation survey, and design a pilot and feasibility study for prospective tracking of patient outcomes using existing prospectively collected inter-hospital and provincial databases.